2022
DOI: 10.1055/s-0042-1758198
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology in Medicine: Development and Validation of an Adapted System Usability Scale (SUS) Questionnaire and Modified Technology Acceptance Model (TAM) to Evaluate User Experience and Acceptability of a Mobile Application in MRI Safety Screening

Abstract: Background Magnetic resonance imaging (MRI) safety screening is a crucial procedure for patient preparation before entering into MRI room. Many hospitals in Malaysia are still using the MRI safety checklist printed form. Besides, clinicians will not get a definite conclusion about whether the patient is contraindicated for MRI or not. Hence, we have created one mobile application named MagnetoSafe to overcome this issue. The application will provide an instant decision on whether the patient has no contraindic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Consistency across different studies and cancer types strengthens the evidence supporting the positive impact of PDAs in healthcare. This study used a mixed-methods approach, followed by Dutch guidelines for lung cancer treatment, and adhered to the IPDAS Evidence Update 2.0 recommendations (15,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistency across different studies and cancer types strengthens the evidence supporting the positive impact of PDAs in healthcare. This study used a mixed-methods approach, followed by Dutch guidelines for lung cancer treatment, and adhered to the IPDAS Evidence Update 2.0 recommendations (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…The 40-item questionnaire, based on elements of the validated System Usability Scale and a study-specific questionnaire (17,18), assessed the performance, potential, and value of the application. Comprehensibility, usability, and the value of the information presented were all considered in the responses about satisfaction with the iPDA.…”
Section: Questionnairementioning
confidence: 99%
“…References in using this research instrument were obtained from the Systematic Literature Review (SLR) process by Kitchenham through analyzing previous research relevant to this study [11]. Based on the SLR, seven studies were found which were used as reference points for evaluating the usability of a banking app [12], e-commerce [13], ShopeePay [14], educational chatbot [15], Mobile Application MRI Safety Screening [16], GCash, Maya, Grabpay [17], and e-wallet applications [18]. In addition, in-depth interviews were also included so as to complement the usability testing.…”
Section: Figure 3 Research Stagesmentioning
confidence: 99%
“…We may assess various goods and services using this questionnaire, including hardware, software, portable electronics, websites, and software applications. As a result of the development of technology, SUS is now a widely accepted industry standard cited in more than 1300 articles and publications [20].…”
Section: Literature Reviewmentioning
confidence: 99%